Motivasi Berolahraga terhadap Prestasi Atlet Bulu Tangkis Putri di Club Ardanoc Purwakarta - Daffa Khairy Hasmahdi; Radika Radika; Aldaffa Farrel Mahardika Sudarso; M. Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Jurnal Porkes, 2026)
This study aims to analyze the effect of sports motivation on the athletic performance of female badminton athletes at Club Ardanoc Purwakarta. This research uses a quantitative correlational approach. The population is all female badminton athletes at Club Ardanoc, totaling 20 athletes, with a sample of 17 athletes selected through purposive sampling. Data were collected using a Likert-scale questionnaire (SS, S, RR, TS, STS) with 25 items measuring six motivation indicators: achievement desire, training enthusiasm, training discipline, self-confidence, environmental support, and training persistence. Athletic performance data were obtained through coach assessments covering playing technique, stroke accuracy, footwork, playing consistency, and match results using a scale of 1–5. Data analysis included validity and reliability tests, normality test, simple linear regression, t-test, and coefficient of determination. Results showed that sports motivation significantly affected female athlete performance (t-count = 5.847 & gt; ttable = 2.131, p & lt; 0.05). The coefficient of determination (R²) was 0.545, meaning that sports motivation contributed 54.5% to athlete performance. The findings suggest that coaches and club managers should design motivation-based training programs to optimize the performance of female badminton athletes.